Health effects of low-dose formaldehyde exposure: a cross-sectional study in occupational settings - Hao-Yi Fan; Jhe-Ping Lin; Ting-An Yang; Yu-Chung Tsao (International Journal of Occupational Medicine and Environmental Health)
Objectives To evaluate the health effects of low-dose formaldehyde exposure in occupational settings, focusing on dermatological and respiratory symptoms and the influence of work tenure.